PENGUKURAN PARTIAL DISCHARGE PADA PEMOHONAN LISTRIK KO-POLIMER ETHYLENE ACRYLIC ACID (EAA) - Hazmi , Ariadi
Abstrack A polymeric material has been used widely as high voltage cable insulation because it has many advantages compared with others. However, partial discharge (PD) often found in polymeric insulation that relate to electrical treeing due to high field between conductor and insulation interface. The electrical treeing is an electrical degradation in polymers. The PD measurement is very important. The measurement used a needle-plane electrode configuration on AC voltage. Furthermore, a computer acts as a controller to obtain and analyze the PD data. The characteristic of PD data has been investigated, namely: pulses number (n), maximum charge ((Lax), average charge (Qa), and cumulative charge (Qtot). The PD data was analyzed by two statistical parameters, kurtosis (Ku) and skewness (SO. The parameters were used to understand the PD characteristic on electrical treeing in Ethylene Acrylic Acid (EAA) Copolymer.